PKM Pelatihan, Perawatan Dan Service Mobil Bagi Siswa STM Di Bengkel Fikry - Ratih Ikha Permata Sari; Anggi Oktaviani; Rini Setiowati; Rina Nurhidayati; Zainal Arifin (Politeknik Kampar, 2023)
This PKM aims to: provide maintenance skills training and car services such as tune-ups and being able to operate repair equipment correctly as well as counseling about the field of managing a business. At an early stage, all students who took part in the training were gathered and given an initial evaluation for see their level of understanding which will later be compared with the test final (post-test). Next, in the activity stage, participants are given material related to car maintenance and service, so that participants will understand about the material presented. The material presented uses methods lectures, discussion methods, demonstrations and direct practice. The last one is final evaluation. The ultimate goal of this service activity is to give knowledge and understanding of how to carry out maintenance and car service. Assessment of the success of this activity is seen through progress knowledge and understanding as well as skills through comparison between tests initial and final tests.